An american marriage - Jones, Tayari (London : One World, 2019)
Newlyweds Celestial and Roy are the embodiment of the American Dream. He is a young executive, and she is an artist on the brink of an exciting career. Until one day they are ripped apart by circumstances neither could have imagined. Roy is arrested and sentenced to twelve years for a crime Celestial knows he didn't commit. Devastated and unmoored, Celestial finds herself struggling to hold on to the love that has been her centre, taking comfort in Andre, their closest friend. When Roy's conviction is suddenly overturned, he returns home ready to resume their life together.
Keywords: Marriage -- Fiction. -- United States; American literature